A tribute: academia in the midst of COVID-19, Professor Dr. Hj. Othman Ismail (Former Dean) - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
When Professor Dr Haji Othman Bin Ismail was appointed as the Dean of Akademi Pengajian Bahasa (APB) on 1st January 2021, the teaching paradigm in the education sector was altered to adapt to the lockdown restrictions. Professor Othman, or more familiar as Prof 0, shared that the essence of being a dean gravitated towards responsibilities and a plethora of challenges. This rings true as he had to devise strategies of continuing to provide training and development, drawing viable alternatives for the conventional mode of instruction of teaching and learning away from the constraint of four walls.